Responsabilidade social corporativa: o que empresas siderúrgicas de MG declaram e quais as percepções desuas comunidades de entorno - Marcelo Aureliano Monteiro de Andrade (2009)
Corporate Social Responsibility (CSR)] is understood as a mechanism which aims to establish an equitable relation between companies and their stakeholders, as well as the commitment of these organizations to the environmental sustainability of their activities. At present, it can beobserved that there is an increasingly more ostensive use of this discourse by private organizations, where they present themselves as being concerned about ethical issues, the environment and the quality of life experienced by their public. However, this study and most of the bibliographies analyzed in it hold that what happens, in practice, is that Corporate Social Responsibility is not applied according to the notion of fairness held by the companies and their managers but, instead, is used as a mechanism to strengthen their brands and, at the same time, as a response to external questioning of these corporations, especially in regard to marketing. In this way, CSR, only serves to provide one more mechanism for a company to achieve its traditional goal of making profit. As a result of these factors, the debate about the real function and motivation of CSR has been increasingly gaining space in the academicworld and in society. This dissertation is intended to evaluate how those steel companies in the State of Minas Gerais that make heavy use of social responsibility strategies express themselves on this matter and how they are perceived by the communities in which they operate. This study therefore sought to find out if these companies have managed to attain their goal of being positively regarded both socially and environmentally. The objects of this study were three large steel companies that, according to the newspaper Estado de Minas, achievedprominence in 2007 for being among the top 20 highest-earning companies. In order to achieve this objective, Carrols (1991) Pyramid of Social Responsibility Theorywas used. This proposes that CSR should take place in four areas; economic, legal, ethical and philanthropic. This author suggests that a socially responsible company should satisfactorily comply with each of these requirements, given that each of their various publics will demand actions that are consistent with one or more of them. In the present study, it was proposed that the companies should emphasize their ethical and philanthropical actions in their vehicles of communication in order that these activities are perceived to be the ones most in evidence in the communities in which the companies are located. It was also suggested that this procedure is the one which has the greatest influence in producing a high positive evaluation of the company brand in these communities. The vehicle of communication known as The Corporate Social Balance was used to evaluate company discourse. This is extensively used by large companies nowadays and, itmainly serves as a means of providing accountability and transparency regarding company information on actions in the area of social and environmental responsibility, as well as on financial results. This material was evaluated by using a variety of methodologies for content and photographic analysis. To analyze the perceptions of the companies held by the communities in which they are located, a survey was carried out, by means of a structured questionnaire that used Likert-type statements. This questionnaire, which was used on about 300 persons who lived adjacent to the companies, sought to evaluate how the communities perceive the companies from a CSR point of view, as well as their perception of the companiess brands and the relationship between their perceptions of CSR and the value of the brand. These analyses were carried out by using multivariate statistical methods. The results showed that the organizations give great emphasis to their ethical and philanthropical actions in their communication but showed little concern for either transparency and accountability or for revealing their economic aims or profit targets. It was also confirmed that, even though these companies lacked transparency, their brands are awarded high value in the communities where they are located and that this evaluation wasmainly based on the positive perception of their ethical and philanthropical activities.